ANTROPOSENTRISME DALAM NOVEL KAILASA KARYA JUSUF AN KAJIAN EKOKRITIK - Widya Prana Rini (Jurnal Nusantara Raya, 2022)
Literary works can be used as a means of caring for the earth. Nature is seen as an object so that human treatment of nature does not provide reciprocity. nature is gradually being degraded. Thus, this study focuses on discussing literary works related to the issue of nature being exploited through the agricultural system. The purpose of this study is to reveal what environmental problems are represented in the novel Kailasa by Jusuf AN as a form of ecocriticism. The eco-critical theory which is based on Cheryll Goltfelty's view is used as a reference in discussing the problem of the relationship between literature and the physical environment. Ecocriticism views the basic relationship that all human culture is connected to the physical world, influencing and being influenced by both the biosphere and the ecosphere. The method used is descriptive qualitative method. The result identifies that anthropocentrism causes exploitation of nature and environment in Kailasa. It also identifies that the Kailasa community experienced a change in eco-consciousness to ego-consciousness; the change was motivated by a material-oriented life for economic purposes.